Format Ideal Tindak Lanjut Putusan Mahkamah Konstitusi untuk Mengefektifkan Asas Erga Omnes - Ningrum, Dian Ayu Widya; Al Khanif, Al Khanif; Antikowati, Antikowati (Constitutional Court of the Republic of Indonesia, Indonesia, 2022)
This article aims to find the ideal format to implement the Constitutional Court (MK) decision through the principle of erga omnes. The erga omnes aims to guarantee the protection of human rights for all citizens. However, the principle of erga omnes cannot be implemented properly due to the gap between adressat and the verdict issued by the MK. This inconsistency and disobedient will result in decline of the erga omnes. An ideal system is needed to improve the application of the Constitutional Court's decisions in accordance with the principle of erga omnes. The results showed that to maximize the principle of erga omnes requires cooperation between the MK and other state institutions or adressat. This can be combined with the implementation of judicial deferral and the provision of deadlines for the follow-up of decisions imposed on adressat as a representation of determining legal boundaries and certainty.